Effect of different tumbling marinade treatments on the water status and protein properties of prepared pork chops. (18th November 2014) - Gao, Tian; Li, Jiaolong; Zhang, Lin; Jiang, Yun; Song, Lei; Ma, Ruixue; Gao, Feng; Zhou, Guanghong
Abstract BACKGROUND Recently, in consideration of the rapidly increasing demand for meat products and the trend towards fast food consumption, the prepared boneless pork chop, as a new style of value‐added product, is cut from pork loins and welcomed by consumers after marinating or further cooking. The effect of different tumbling marinade treatments (control group, CG; conventional static marinade, SM; vacuum continuous tumbling marinade, CT; vacuum intermittent tumbling marinade, IT) on the water status and protein properties of prepared pork chops was investigated. RESULTS The CT treatment significantly increased T22 peak area ratio compared with other treatments (P < 0.05). Histological microstructure results showed that CT treatment significantly increased solubility of salt‐soluble proteins and decreased muscle fiber diameter compared with other treatments (P < 0.05). The net enthalpy (ΔH) of IT treatment was significantly lower than SM treatment (P < 0.05), whereas the protein denaturation temperature (Tm3) and ΔH3 of CT treatment were lower than IT treatment. CONCLUSION These results suggest that CT treatment was more effective in improving the water mobility and distribution, promoting the denaturation of muscle protein and accelerating the marinade efficiency of pork chops compared with other treatments. Thus CT treatment should be adopted. © 2014 Society of Chemical Industry